IMPLEMENTASI PROGRAM BIMBINGAN KARIR UNTUK MEMPERSIAPKAN SISWA SMK EL MOSTHOFA MEMASUKI DUNIA KERJA - Jalaluddin Madani Jalaluddin Madani (Jurnal Pendidikan Nusantara, 2024)
Career guidance programmes play an important role in helping students plan and develop their future careers, especially at vocational secondary schools that are oriented towards work readiness. This study aims to describe the implementation of a career guidance programme to prepare students at SMK El Mosthofa for the world of work, as well as the effectiveness and obstacles encountered in this career guidance programme. This research uses a qualitative approach. In this study, the researcher will observe and interview teachers and students using instruments that have been prepared. Data collection techniques include observation, interviews, and distribution of questionnaires. The results show that the career guidance programme at SMK El Mosthofa has been implemented quite well. The strategies employed include providing career information services, group counselling, and developing students' vocational skills. The programme is effective in enhancing students' career readiness, as evidenced by more focused career planning, improved understanding of the workplace, and an increase in the number of graduates employed in the workforce, reaching 65% of the 75 graduates. However, the study also identified several challenges, such as limited facilities and infrastructure, and a shortage of career counsellors exceeding the ideal number. Therefore, it can be concluded that the implementation of the career guidance programme at SMK El Mosthofa provides significant benefits for students in preparing themselves to enter the workforce. Despite some obstacles, the programme can be optimised with better management and adequate support.